Analyse de l’étendue des pouvoirs d’un syndic sur le REER d’un failli - Boucher, Bernard; Sibre, Hubert (Assurances, 1995)
RRSPs are so popular that for the 1988 taxation year, Canadians had already invested $1,869,042,000 in various types of registered retirement savings plans. As a result, when it comes to personal bankruptcies, trustees must ask themselves how to treat the sums accumulated in the RRSPs of bankrupt individuals. In this article, the authors examine two issues: Are RRSPs part of assets to be distributed to creditors and can sums withdrawn from an RRSP prior to a bankruptcy be retrieved for their benefit?